Mario Vargas Llosa: Approach to the encounter of his essay writing (1972-2015) - Morales Mena, Javier (2017)
The intellectual production of Mario Vargas Llosa (1936) is not restricted to a single literary genre. While his role as novelist is one of the most studied, he is also author of plays and political and literary essays. When the reception of his texts is reviewed, a significant percentage of attention is captured in his narrative and ditto for, although to a lesser extent, his plays. In contrast, the reception on his literary essay texts is very scarce. It is precisely for that reason, to contribute to the knowledge of this essay production and reception of the same, this article presents the thesis of epistemological void of Angel Rama, the thesis of autoreferentiality of José Miguel Oviedo and the thesis of conceptual approval of Sara Castro-Klarén . These are approaches which start in the 1970s and continue until the end of the 1980s; and to complement the interval of reception until today, we present the review of these theses in Ewa Kobylecka-Piwonska, Mabel Moraña, Belen Castañeda and Raymond L. Williams. This explanation about the issue allows to know what the problems that have been set through these decades of critical reception on Vargas Llosa intellectual production.